(untitled) (Faridpur Medical College Journal, 2012)
Haemorrhoids are one of the most common anorectal disorders. Conventional haemorrhoidectomy (CH) is the most commonly practiced surgical technique. Stapled haemorrhoidopexy (SH) [procedure for prolapsed haemorrhoids (PPH)] is newly developed method for the surgical management of Haemorrhoids. This review looks at the surgical management of prolapsed haemorrhoids in light of this recent development and suggests a treatment approach based on this current evidence. A Medline, Pubmed and Cochrane data base search was performed using key words "haemorrhoid" or ’hemorrhoid’ and staple. Relevant papers e.g. randomized controlled trials, review and metaanalyses from different parts of the world were collected. Data were analyzed and compiled. Though early small RCTs (stapled haemorrhoidopexy comparing with traditional excisional surgery) have shown stapled haemorrhoidopexy is less painful and it is associated with quicker recovery but recent large meta-analyses and long term follow up have shown SH is associated with a higher long term risk of haemorrhoid recurrence and symptoms of prolapse. DOI: http://dx.doi.org/10.3329/fmcj.v7i1.10297 Faridpur Med. Coll. J. 2012;7(1): 37-41